Interface treating agent as well as preparation method and application thereof

By using components such as cement, fly ash, mineral powder, nano powder and hydroxypropyl methylcellulose ether in the interface treatment agent, combined with specific preparation methods, the bonding properties of the interface treatment agent in the prior art are solved and The problem of insufficient anti-chlorine salt corrosion performance has achieved efficient concrete interface bonding and anti-chlorine salt corrosion performance, which is suitable for bridge repair.

CN119306436APending Publication Date: 2025-01-14ZHENGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411481643.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing concrete interface treatment agents have shortcomings in the bonding properties of old and new concretes and the resistance to chlorine salt corrosion, and are not suitable for the repair of concrete structures in coastal corrosion environments.

Method used

Using a formulation of an interfacial treatment agent, including cement, fly ash, mineral powder, nano-micro powder, hydroxypropyl methylcellulose ether and water reducer, prepared by specific mixing and stirring steps to form a high bond strength and interfacial treatment agent with anti-chlorine salt corrosion properties.

Benefits of technology

It significantly improves the bonding and compressive strength of concrete, is suitable for wide-split bridges, has good affinity and bonding strength, while reducing costs and is easy to use in engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097864680000011
    Figure BDA0005097864680000011
  • Figure BDA0005097864680000021
    Figure BDA0005097864680000021
  • Figure BDA0005097864680000031
    Figure BDA0005097864680000031
Patent Text Reader

Abstract

The invention provides an interface treating agent as well as a preparation method and application thereof, and belongs to the technical field of concrete. The interface treating agent is prepared from the following raw materials: 40 to 55 parts of cement, 6 to 15 parts of fly ash, 6 to 15 parts of mineral powder, 3 to 10 parts of silica fume, 0.05 to 0.2 part of hydroxypropyl methyl cellulose ether, 10 to 15 parts of nano micro powder, 0.01 to 0.1 part of calcium carbide slurry, 1 to 3 parts of water reducing agent and 30 to 45 parts of water. The interface treating agent disclosed by the invention can be used for remarkably improving the binding power and chlorine salt corrosion resistance of the widened bridge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an interface treatment agent and a preparation method and application thereof. Background Art

[0002] In the construction, renovation and reinforcement of bridges, tunnels and houses, the bonding problem of the interface between new and old concrete is often involved. The bonding surface between new and old concrete is the weak part of the overall structure, which is prone to cracks caused by uncoordinated shrinkage strain, which is then corroded by chloride salts in seawater, causing steel bars to rust and lead to structural failure. In order to enhance the bonding quality between new and old concrete, the most commonly used method in engineering is to apply interface treatment agent on the surface of old concrete before pouring new concrete.

[0003] According to the main components, interface treatment agents can be divided into inorganic interface agents and organic interface agents. Inorganic interface agents are mainly cement paste or inorganic (fly ash, silica fume, slag, expansion agent, etc.) modified cement paste. Inorganic interface agents are not conducive to the durability of bonding due to the shrinkage characteristics and pore structure defects of the cement paste itself. Organic interface agents add organic polymers such as epoxy resin, styrene-butadiene emulsion or propylene emulsion to inorganic interface agents to form a dense spatial network structure with the hydration products, thereby improving the bonding strength of new and old concrete. However, the construction operation of organic interface agents is complicated, the price is expensive, and the cost of promotion and application is high. Organic modified interface agents can only improve the bonding performance, ignoring the bonding durability of the interface agent, and are not suitable for repairing concrete structures in coastal corrosive environments.

[0004] Therefore, it is of great significance and value to develop a concrete interface treatment agent that has both excellent bonding properties and high resistance to chloride salt corrosion. Summary of the invention

[0005] The purpose of the present invention is to provide an interface treatment agent and a preparation method and application thereof, so as to solve the technical problems of poor adhesion and anti-chloride salt corrosion performance of the interface treatment agent in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides an interface treatment agent, comprising the following raw materials in parts by weight:

[0008]

[0009]

[0010] Furthermore, the mineral powder includes S75 mineral powder and / or S95 mineral powder.

[0011] Furthermore, the molecular weight of the hydroxypropyl methylcellulose ether is 50,000 to 150,000.

[0012] Furthermore, the nano powder includes one or more of nano silicon dioxide powder, nano aluminum oxide powder, nano sodium silicate powder and nano sodium carbonate powder;

[0013] The particle size of the nano powder is 1 to 100 nm.

[0014] Furthermore, the water reducer includes an aminosulfonate water reducer or a polycarboxylate water reducer.

[0015] The present invention provides a method for preparing the interface treatment agent, comprising the following steps:

[0016] (1) Mixing cement, fly ash, mineral powder, silica fume and nano powder to obtain a dry powder mixture;

[0017] (2) dissolving hydroxypropyl methylcellulose ether and a water reducing agent in part of water to form a uniform solution, and then adding the dry powder mixture into the solution and mixing to obtain a mixed solution;

[0018] (3) Add calcium carbide mud and the remaining water into the mixed solution and mix to obtain an interface treatment agent.

[0019] Furthermore, in the step (1) and the step (3), the mixing is carried out during stirring, the stirring speed is independently 30 to 50 r / min, and the stirring time is independently 1 to 3 min.

[0020] Furthermore, in the step (2), the mixing is carried out during stirring, the stirring speed is 60 to 70 r / min, and the stirring time is 1 to 5 min.

[0021] Furthermore, the mass ratio of the partial water to the remaining water is 1-3:1-3.

[0022] The invention also provides an application of the interface treatment agent in widening a bridge.

[0023] Beneficial effects of the present invention:

[0024] The hydroxypropyl methylcellulose ether of the present invention can increase the viscosity of concrete in the interface treatment agent, and prolong the operable time of concrete by regulating the viscosity and setting rate of cement paste, and avoid slurry flow and pore blocking, thereby improving the mechanical properties of concrete such as compressive strength. At the same time, the hydroxypropyl methylcellulose ether is used in combination with a water reducing agent to further improve the mechanical properties of concrete. The present invention utilizes the huge activity of nanoparticles to reduce the Ca(OH) 2The coarse particles are formed and arranged in a directional manner, thereby greatly improving the interface bonding strength. The interface treatment agent of the present invention can effectively improve the interface bonding strength by controlling the ratio of each component, is suitable for widening bridges, has good affinity and bonding strength, is low in price, and is easy to use in engineering. DETAILED DESCRIPTION

[0025] The present invention provides an interface treatment agent, comprising the following raw materials in parts by weight:

[0026]

[0027] In the present invention, the content of the cement is preferably 42 to 52 parts by weight, and more preferably 45 to 50 parts by weight.

[0028] In the present invention, the content of the fly ash is preferably 7 to 12 parts by weight, and more preferably 8 to 10 parts by weight.

[0029] In the present invention, the content of the mineral powder is preferably 7 to 12 parts by weight, and more preferably 8 to 10 parts by weight.

[0030] In the present invention, the mineral powder includes S75 mineral powder and / or S95 mineral powder.

[0031] In the present invention, the content of the silica fume is preferably 4 to 9 parts by weight, and more preferably 5 to 8 parts by weight.

[0032] In the present invention, the content of the hydroxypropyl methylcellulose ether is preferably 0.08 to 0.18 parts by weight, and more preferably 0.1 to 0.15 parts by weight.

[0033] In the present invention, the molecular weight of the hydroxypropyl methylcellulose ether is 50,000 to 150,000, preferably 60,000 to 130,000, and more preferably 80,000 to 120,000.

[0034] In the present invention, the content of the nano powder is preferably 11 to 14 parts by weight, and more preferably 12 to 13 parts by weight.

[0035] In the present invention, the nano powder includes one or more of nano silicon dioxide powder, nano aluminum oxide powder, nano sodium silicate powder and nano sodium carbonate powder, preferably one or more of nano silicon dioxide powder, nano aluminum oxide powder and nano sodium carbonate powder, and more preferably nano silicon dioxide powder and / or nano aluminum oxide powder;

[0036] The particle size of the nano powder is 1 to 100 nm, preferably 5 to 90 nm, and more preferably 10 to 80 nm.

[0037] In the present invention, the content of the calcium carbide mud is preferably 0.02 to 0.08 parts by weight, and more preferably 0.04 to 0.06 parts by weight.

[0038] In the present invention, the content of the water reducing agent is preferably 1.2 to 2.8 parts by weight, and more preferably 1.5 to 2.5 parts by weight.

[0039] In the present invention, the water reducer includes aminosulfonate water reducer or polycarboxylate water reducer, preferably polycarboxylate water reducer.

[0040] In the present invention, the water content is preferably 32 to 43 parts by weight, and more preferably 35 to 40 parts by weight.

[0041] The present invention provides a method for preparing the interface treatment agent, comprising the following steps:

[0042] (1) Mixing cement, fly ash, mineral powder, silica fume and nano powder to obtain a dry powder mixture;

[0043] (2) dissolving hydroxypropyl methylcellulose ether and a water reducing agent in part of water to form a uniform solution, and then adding the dry powder mixture into the solution and mixing to obtain a mixed solution;

[0044] (3) Add calcium carbide mud and the remaining water into the mixed solution and mix to obtain an interface treatment agent.

[0045] In the present invention, in step (1) and step (3), mixing is carried out during stirring, and the stirring speed is independently 30 to 50 r / min, preferably 32 to 48 r / min, and more preferably 35 to 45 r / min; the stirring time is independently 1 to 3 min, preferably 1.2 to 2.7 min, and more preferably 1.5 to 2.5 min.

[0046] In the present invention, in the step (2), mixing is carried out under stirring, the stirring speed is 60 to 70 r / min, preferably 63 to 68 r / min, and more preferably 65 r / min; the stirring time is 1 to 5 min, preferably 1.5 to 4.5 min, and more preferably 2 to 4 min.

[0047] In the present invention, the mass ratio of the partial water to the remaining water is 1-3:1-3, preferably 1.1-2.8:1.1-2.8, and more preferably 1.3-2.5:1.3-2.5.

[0048] The invention also provides an application of the interface treatment agent in widening a bridge.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] 50 parts of cement, 10 parts of fly ash, 10 parts of S75 mineral powder, 10 parts of silica fume and 12 parts of nano-silicon dioxide powder with a particle size of 50 nm were mixed, and the mixing was carried out under stirring at a stirring speed of 40 r / min and a stirring time of 2 min to obtain a dry powder mixture;

[0052] 0.1 parts of hydroxypropyl methylcellulose ether with a molecular weight of 100,000 and 2 parts of polycarboxylate water reducer (the manufacturer of the polycarboxylate water reducer is Shandong Wanhua Tianhe New Materials Co., Ltd.) were dissolved in 15 parts of water to form a uniform solution, and then the dry powder mixture was added to the solution and mixed, and the mixing was carried out under stirring at a speed of 65 r / min and a stirring time of 3 min to obtain a mixed solution;

[0053] 0.05 parts of calcium carbide mud and 20 parts of water are added to the mixed solution and mixed. The mixing is carried out while stirring. The stirring speed is 40 r / min and the stirring time is 2 minutes to obtain an interface treatment agent.

[0054] Example 2

[0055] 50 parts of cement, 10 parts of fly ash, 10 parts of S75 mineral powder, 10 parts of silica fume and 12 parts of nano-silicon dioxide powder with a particle size of 50 nm were mixed, and the mixing was carried out under stirring at a stirring speed of 40 r / min and a stirring time of 2 min to obtain a dry powder mixture;

[0056] 0.08 parts of hydroxypropyl methylcellulose ether with a molecular weight of 150,000 and 2 parts of polycarboxylate water reducer (the manufacturer of the polycarboxylate water reducer is Shandong Wanhua Tianhe New Materials Co., Ltd.) were dissolved in 15 parts of water to form a uniform solution, and then the dry powder mixture was added to the solution and mixed, and the mixing was carried out under stirring at a speed of 65 r / min and a stirring time of 3 min to obtain a mixed solution;

[0057] 0.03 parts of calcium carbide mud and 20 parts of water are added to the mixed solution and mixed. The mixing is carried out while stirring. The stirring speed is 40 r / min and the stirring time is 2 minutes to obtain an interface treatment agent.

[0058] Example 3

[0059] 50 parts of cement, 10 parts of fly ash, 12 parts of S95 mineral powder, 8 parts of silica fume and 12 parts of nano-silicon dioxide powder with a particle size of 50 nm were mixed, and the mixing was carried out under stirring at a stirring speed of 40 r / min and a stirring time of 2 min to obtain a dry powder mixture;

[0060] 0.15 parts of hydroxypropyl methylcellulose ether with a molecular weight of 50,000 and 2 parts of polycarboxylate water reducer (the manufacturer of the polycarboxylate water reducer is Shandong Wanhua Tianhe New Materials Co., Ltd.) were dissolved in 15 parts of water to form a uniform solution, and then the dry powder mixture was added to the solution and mixed, and the mixing was carried out under stirring at a speed of 65 r / min and a stirring time of 3 min to obtain a mixed solution;

[0061] 0.05 parts of calcium carbide mud and 20 parts of water are added to the mixed solution and mixed. The mixing is carried out while stirring. The stirring speed is 40 r / min and the stirring time is 2 minutes to obtain an interface treatment agent.

[0062] Example 4

[0063] 50 parts of cement, 10 parts of fly ash, 10 parts of S75 mineral powder, 10 parts of silica fume and 12 parts of nano-silicon dioxide powder with a particle size of 50 nm were mixed, and the mixing was carried out under stirring at a stirring speed of 30 r / min and a stirring time of 2 min to obtain a dry powder mixture;

[0064] 0.1 parts of hydroxypropyl methylcellulose ether with a molecular weight of 100,000 and 2 parts of polycarboxylate water reducer (the manufacturer of the polycarboxylate water reducer is Shandong Wanhua Tianhe New Materials Co., Ltd.) were dissolved in 15 parts of water to form a uniform solution, and then the dry powder mixture was added to the solution and mixed, and the mixing was carried out under stirring at a speed of 60 r / min and a stirring time of 4 min to obtain a mixed solution;

[0065] 0.05 parts of calcium carbide mud and 20 parts of water are added to the mixed solution and mixed. The mixing is carried out while stirring. The stirring speed is 50 r / min and the stirring time is 2 minutes to obtain an interface treatment agent.

[0066] Comparative Example 1

[0067] Compared with Example 1, the difference is that the hydroxypropyl methylcellulose ether in Example 1 is replaced by polypropylene fiber.

[0068] Comparative Example 2

[0069] Compared with Example 1, the difference is that in Comparative Example 2, no nano powder is added.

[0070] Comparative Example 3

[0071] Compared with Example 1, the difference is that the weight portion of hydroxypropyl methylcellulose ether in Comparative Example 3 is 0.02 parts.

[0072] Comparative Example 4

[0073] Compared with Example 1, the difference is that the weight portion of hydroxypropyl methylcellulose ether in Comparative Example 4 is 0.5 parts.

[0074] Comparative Example 5

[0075] Compared with Example 1, the difference is that the weight proportion of the nano-powder in Comparative Example 5 is 5 parts.

[0076] The performance of the interface treatment agents prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was tested according to JC / T 907-2002 standard. The test results are shown in Table 1.

[0077] Table 1 Performance test results of the interface treatment agents prepared in Examples 1 to 4 and Comparative Examples 1 to 5

[0078]

[0079] As can be seen from the above embodiments, the present invention provides an interface treatment agent and its preparation method and application, comprising the following raw materials: 40-55 parts of cement, 6-15 parts of fly ash, 6-15 parts of mineral powder, 3-10 parts of silica fume, 0.05-0.2 parts of hydroxypropyl methylcellulose ether, 10-15 parts of nano-powder, 0.01-0.1 parts of calcium carbide mud, 1-3 parts of water reducer, and 30-45 parts of water. The interface treatment agent of the present invention can significantly increase the bonding force and chloride salt corrosion resistance of the widened bridge.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An interface treatment agent, characterized in that Contains the following raw materials by weight:

2. The interface treatment agent according to claim 1, characterized in that The mineral powder includes S75 mineral powder and / or S95 mineral powder.

3. The interface treatment agent according to claim 1 or 2, characterized in that: The molecular weight of the hydroxypropyl methylcellulose ether is 50,000 to 150,000.

4. The interface treatment agent according to claim 3, characterized in that: The nano powder includes one or more of nano silicon dioxide powder, nano aluminum oxide powder, nano sodium silicate powder and nano sodium carbonate powder; The particle size of the nano powder is 1 to 100 nm.

5. The interface treatment agent according to claim 1, 2 or 4, characterized in that: The water reducer includes an aminosulfonate water reducer or a polycarboxylate water reducer.

6. A method for preparing the interface treatment agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mixing cement, fly ash, mineral powder, silica fume and nano powder to obtain a dry powder mixture; (2) dissolving hydroxypropyl methylcellulose ether and a water reducing agent in part of water to form a uniform solution, and then adding the dry powder mixture into the solution and mixing to obtain a mixed solution; (3) Add calcium carbide mud and the remaining water into the mixed solution and mix to obtain an interface treatment agent.

7. The preparation method according to claim 6, characterized in that: In the steps (1) and (3), the mixing is performed during stirring, the stirring speed is independently 30 to 50 r / min, and the stirring time is independently 1 to 3 min.

8. The preparation method according to claim 7, characterized in that: In the step (2), the mixing is carried out during stirring, the stirring speed is 60 to 70 r / min, and the stirring time is 1 to 5 min.

9. The preparation method according to claim 7 or 8, characterized in that: The mass ratio of the partial water to the remaining water is 1-3:1-3.

10. Use of the interface treatment agent according to any one of claims 1 to 5 in widening a bridge.